2020
DOI: 10.29219/fnr.v64.3589
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effects of a lipophilic extract obtained from flowers of Wisteria sinensis by activating Akt/GLUT4 and Akt/GSK3β

Abstract: Background: Type 2 diabetes mellitus is primarily caused by insulin resistance (IR) in insulin-sensitive tissues, including liver, white adipose tissues (WAT), and skeletal muscles. Discovering nutritious foods with antidiabetic effects is of great significance. Numerous published reports indicated that protein kinase B (Akt) and glucose transporter 4 (GLUT4) play crucial roles in ameliorating IR and diabetic symptoms. Objective: In the present study, antidiabetic effects and the potential mechanism of action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Type 2 diabetes mellitus (T2DM) is the most prevalent form of diabetes, accounting for 90% of diabetes cases, 1 and is characterized by hyperglycemia and insulin deficiency caused by β-cell dysfunction and insulin resistance (IR) in various target organs, including the liver, heart, skeletal muscle, and adipose tissue. [2][3][4][5][6] After a meal, insulin secreted from the pancreas triggers a systemic metabolic response involving the joint efforts of insulin target tissues, including the liver, muscle, and adipose tissues. 7 High blood glucose levels in tissues with active redox cellular functions lead to generation of reactive oxygen species (ROS), which causes oxidative stress damage, particularly in the liver, pancreas, and kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is the most prevalent form of diabetes, accounting for 90% of diabetes cases, 1 and is characterized by hyperglycemia and insulin deficiency caused by β-cell dysfunction and insulin resistance (IR) in various target organs, including the liver, heart, skeletal muscle, and adipose tissue. [2][3][4][5][6] After a meal, insulin secreted from the pancreas triggers a systemic metabolic response involving the joint efforts of insulin target tissues, including the liver, muscle, and adipose tissues. 7 High blood glucose levels in tissues with active redox cellular functions lead to generation of reactive oxygen species (ROS), which causes oxidative stress damage, particularly in the liver, pancreas, and kidney.…”
Section: Introductionmentioning
confidence: 99%
“…A high-calorie diet and obesity are the main risk factors for T2DM. , In the present study, HFD-fed mice showed an increase in body weight, induction of both insulin resistance, and glucose tolerance that may mimic the human lifestyle. Streptozotocin is selectively toxic to the insulin-producing β cells of the pancreas in mammals and has been long injected in experimental animals for the reproduction of diabetes pathology in humans . Multiple methods of STZ dosing depend on the type and the severity of diabetes in mice, and the dose range also varies largely, so they are applied in various ways from 100 to 200 mg/kg in a single high dose.…”
Section: Resultsmentioning
confidence: 72%
“…Zen 2010 Software (Carl Zeiss, Jena, Germany) was used to analyze the fluorescence intensity of mOrange. The detailed method of GLUT-4 fusion with the plasma membrane was described in previous reports [ 24 ].…”
Section: Methodsmentioning
confidence: 99%